The SAGE handbook of aging, work and society - Burke, Ronald J.; Field, John 1949-; Burke, Ronald J.; Cooper, Cary L. (London SAGE, 2013)
Key international contributors come together to create a definitive map of the subject. Framed by an authoritative introductory chapter, 'The SAGE Handbook of Aging, Work and Society' offers a critical overview of the most significant themes and topics, with discussions of current research, theoretical controversies and emerging issues.
The Aging Workforce: Individual, Organizational and Societal Opportunities and Challenges Aging, Work and the Demographic Dividend in South Asia Age and Generational Differences in Work Psychology: Facts, Fictions, and Meaningful Work Comparative Age Management: Theoretical Perspectives and Practical Implementations Making a Case for the Existence of Generational Stereotypes: A Literature Review and Exploratory Study Demographic Challenges for Human Resource Management: Implications from Management and Psychological Theories Age Stereotypes in the Workplace: Multidimensionality, Cross-cultural Applications, and Directions for Future Research The Role of Social Networking Games in Maintaining Intergenerational Communications for Older Adults Older Workers, Occupational Stress and Safety Reconstructing Work and Retirement: Labour Market Trends and Policy Issues Training Older Workers: A Review Older Workers in the Professions: Learning Challenges and Strategies Learning in Later Life Quality of Work, Wellbeing and Retirement Working Caregivers in the 'Sandwiched Generation' Engaging Elders in Community and Society The Social Connections of Older Europeans Care Work and New Technologies of Care for Older People Living at Home Policies for Older Adult Learning: The Case of the European Union World Population in HIstorical Perspective New Patterns of Late-Career Employment Legal Aspects of Age Discrimination Age and Work Motives Optimizing the Long Future of Aging: Beyond Involvement to Engagement Work Performance and the Older Worker Research on Age Diversity in the Workforce: Current Trends and Future Research Directions Migration and Workforce Aging The Measurement of Multiple Dimensions of Subjective Well-being in Later Life Prolonging Working Life in an Aging World: A Cross-national Perspective on Labor Market and Welfare Policies Toward Active Aging Malcolm Sergeant. Chris Phillipson -- Stina Johansson -- Bram Vanhoutte -- Franz Kolland and Anna Wanka -- Jacquelyn Boone James, Marcie Pitt-Catsouphes, Jennifer Kane Coplon and Betty Eckhaus Cohen -- Yunan Chen, Jing Wen and Bo Xie -- Marvin Formosa -- Elissa L. Perry, Apivat Hanvongse and Danut A. Casoinic -- Gary A. Adams, Sarah DeArmond, Steve M. Jex and Jennica R. Webster -- Penny Vera-Sanso -- Ronald J. Burke, Cary Cooper and John Field -- Tommy Bengtsson and Kirk Scott -- Florian Kunze and Stephen A. Boehm -- Anne-Marie Guillemard -- John Field -- Margaret E Beire and Ruthe Kanfer -- Cort W. Rudolph, Boris B. Baltes and Keith L. Zabel -- Kerr Inkson, Margaret Richardson and Carla Houkamau -- Celia Roberts, Maggie Mort and Christine Milligan -- Martil Kohli and Harald Künemund -- Paul Fairlie -- Stephan A. Boehm, Heike S. Schröder and Florian Kunze -- Birgit Verworn, Christiane Hipp and Doreen Weber -- Richard A. Posthuma and Laura Guerrero -- Yu-Shan Hsu -- Tare Fenwick -- Johannes Siegrist and Morten Wahrendorf -- Margaret B. Neal, Leslie B. Hammer, Ayala Malach Pines, Todd E. Bodner and Melissa L. Cannon --
Electronic reproduction.
Keywords: Age and employment; Older people -- Employment; Older people -- Social conditions; Electronic books